2022
DOI: 10.1109/tcad.2021.3054811
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Batch-Constrained Bayesian Optimization Approach for Analog Circuit Synthesis via Multiobjective Acquisition Ensemble

Abstract: Bayesian optimization is a promising methodology for analog circuit synthesis. However, the sequential nature of the Bayesian optimization framework significantly limits its ability to fully utilize real-world computational resources. In this paper, we propose an efficient parallelizable Bayesian optimization algorithm via Multi-objective ACquisition function Ensemble (MACE) to further accelerate the optimization procedure. By sampling query points from the Pareto front of the probability of improvement (PI), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 54 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…It can be seen that the proposed algorithm gives a better optimal area than the ones reported in [12], [19]. The proposed method has been used for the design of the op-amp reported in [7] for an unconstrained optimisation in 180 nm technology and the comparison with the reported Bayesian optimisation method is given in Table V. It shows that the proposed technique converges to a higher fitness function value showing a better performance.…”
Section: Simulation Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…It can be seen that the proposed algorithm gives a better optimal area than the ones reported in [12], [19]. The proposed method has been used for the design of the op-amp reported in [7] for an unconstrained optimisation in 180 nm technology and the comparison with the reported Bayesian optimisation method is given in Table V. It shows that the proposed technique converges to a higher fitness function value showing a better performance.…”
Section: Simulation Resultsmentioning
confidence: 85%
“…Since the state-of-the-art transistors have really complex mathematical models, the problem becomes even more challenging. In recent studies [6], [7], Bayesian optimisation methods have been reported for automated analog circuit sizing. Another class of algorithms, called the evolutionary algorithms (EAs) have been reported to be used in analog circuit optimisation.…”
Section: Introductionmentioning
confidence: 99%
“…Local BO, sparse GPR model [85] GNN + WEI Amp (C-2, D-8), driver (C-1, D-6) Parasitic-aware, GNN w/ dropout [86] GPR + Acq ensemble Amp-1,2,3 (C-10, C-12, C-24), etc., Batch BO enabled by the ensemble [87] Add-GPR + UCB Amp, DC (C-na) LDE-aware, high-dimensional [89] GPR + WEI Op-Amp (C-na) Bi-level BO, compensation design [90] GPR + EI Amp-1,2 (C-10, C-12) Local penalization 1 [92] GPR + modified TS Amp-1,2 (C-11, C-43) Applied to technology migration [105] Online GPR Op-Amp-1,2 (C-11, C-21) Self-adaptive incremental learning [102] GPR + wPESC Amp-1,2 (C-10, C-11) Automatically choose test benches [103] GPR + EIM Op-Amp-1,2 (C-11, C-21) Asynchronous BO [104] Online GPR + EIM Op-Amp-1,2 (C-11, C-26), etc., Self-adaptive incremental learning [100] GPR + LCB/EI CP (C-36), Amp (C-12) Search in one-dimensional subspace [101] MT-GPR + EI Transformer (C-4), LNA (C-15), etc., Multitask NN as GPR kernel [229] GPR + WEI 5 OTAs, 2 VCOs, 2 SCFs (D-na), etc., Wire sizing, GPR guided by GNN [96] GPR + LCB Voltage regulator (C-17 + D-10), etc., Novel evolutionary algorithm [97] GPR + TS LNA (C/D-17) 2…”
Section: B Other Problems and Discussionmentioning
confidence: 99%
“…While a broad variety of MOO approaches in black box environments deals with effective algorithms, only few of them meet the efficiency criterion [2]. Specifically Bayesian Optimization (BO) [3][4][5][6] algorithms based on Gaussian Process Regression (GPR) [3,[7][8][9] appear as interesting effective and efficient MOO candidates.…”
Section: Design Of Complex Power Systemsmentioning
confidence: 99%
“…By Theorem 3, we obtain a Gaussian Process for each i. In case the covariance function involves the choice of some hyperparameter, we determine that parameter by solving Equation (5). Next, we condition each mean m i and covariance function C i to T using Equations ( 2) and (3), respectively.…”
Section: Setting Up the Gprsmentioning
confidence: 99%